THE HUARPA OCCUPATION IN TAMBO, LA MAR - Pérez Calderón, Ismael (2015)
We present a set of information existing in the upper course of Torobamba river, the main tributary of the Pampas river, northeastern Ayacucho archaeological sites. The sites are located between 2800 and 4250 in the province of the Sea or eastern flank of the Cordillera del Razuwillcca, which connects with the Apurimac, unexplored space for at least 3 decades, following the violent events that occurred in Uchuracay, the distribution of settlements shows that it was not just old path area residents who moved into the jungle but was a territory with a dense population, especially during Huarpa and Huari (200 AD-1200 AD) eras, whose states should control the use of existing resources, if minerals, agricultural products and livestock. We complement the ethnographic record information and data from private collections.